2006
DOI: 10.1161/01.str.0000226897.43749.27
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Activation and Outcome After Recombinant Tissue Plasminogen Activator Therapy for Acute Ischemic Stroke

Abstract: for the NINDS rtPA Stroke Study Group Background and Purpose-Early thrombolytic therapy with intravenous recombinant tissue plasminogen activator (rtPA) improves clinical outcome in acute ischemic stroke (AIS), but impaired endogenous fibrinolysis, thrombin generation, and vascular injury may hamper the efficacy of thrombolysis. We investigated in an exploratory, post hoc analysis the relationship between hemostatic markers and clinical outcomes among patients included in the National Institute of Neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 32 publications
2
43
2
1
Order By: Relevance
“…8 Finally, a recent study found an association between hemostatic activation and clinical outcome. 3 Although we also found a dynamic change in these hemostatic markers, we were unable to find an association between the level of these markers and the likelihood of recanalization. One limitation of our study is the small sample of patients.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…8 Finally, a recent study found an association between hemostatic activation and clinical outcome. 3 Although we also found a dynamic change in these hemostatic markers, we were unable to find an association between the level of these markers and the likelihood of recanalization. One limitation of our study is the small sample of patients.…”
Section: Discussioncontrasting
confidence: 63%
“…1,2 One hypothesis is that efficient recanalization is likely only if certain changes in hemostatic levels are achieved in comparison with baseline levels. A recently reported study suggested that hemostatic activation is associated with clinical outcome in patients treated with intravenous rtPA, 3 although no data about vascular patency was provided.…”
mentioning
confidence: 99%
“…[671][672][673][674][675] A higher hematocrit is associated with reduced reperfusion, greater infarct size, and higher mortality among patients after ischemic stroke. 671,674 Hemodilution and volume expansion are proposed as treatment options to reduce the viscosity of blood, improve flow through collateral channels and microvascular circulation, and increase oxygen-carrying capacity.…”
Section: Hypervolemia and Hemodilution For Treatment Of Acute Ischemimentioning
confidence: 99%
“…10,11 Reocclusion after tPA treatment is induced, at least in part, by the activation of the coagulation cascade by tPA. 12,13 These findings indicate that the use of antiplatelet drugs is potentially a double-edged sword in the context of tPA treatment; that is, use of antiplatelet agents is likely to be beneficial for stroke outcome despite increased risk of hemorrhagic infarction. Consistent with these findings, a randomized controlled trial in the Netherlands has shown that thrombolysis in combination with antiplatelet drugs prevented reocclusion and improved the clinical outcome.…”
mentioning
confidence: 98%